Belarus on the path to a green and circular economy: a comparison with the European Green Deal - Anna Gorbatcheva; Nikolai Gorbatchev; Siarhei Zenchanka (Academia Green Energy)
This article assesses Belarus’ advancement toward green and circular economics in comparison with the ambitious objectives defined in the European Green Deal (EGD). Through an analysis of the country’s current environmental policies, regulatory framework, technological advancements, and resource management strategies, this study provides a comprehensive overview of Belarus’ positioning on the transformative path toward sustainability. In parallel, key aspects such as policy alignment, international cooperation, and challenges are explored to elucidate Belarus’ concerted efforts in fostering a greener and more circular economy. The discussion encompasses the capacity-building needs, transition challenges, and market integration considerations crucial for Belarus to align its strategies with European standards and market demands. However, a notable disadvantage of Belarusian regulations is the absence of a single comprehensive document akin to the EGD. This absence may pose challenges in standardizing and streamlining Belarus’ environmental and sustainability initiatives within a unified framework, potentially impacting the coherence and efficiency of the country’s green and circular economy strategies.